Ex-Templars in England - Forey, Alan (The journal of ecclesiastical history, 2002)
After their trial, Templars in England were in 1311 dispatched singly to religious houses, where they were to observe their vows and do penance. Although there was some opposition from both Templars and monasteries, the payment of pensions assigned to Templars caused longer-lasting problems: the crown and later the Hospitallers frequently defaulted in making payment from former Templar revenues. In 1318 John XXII instructed that Templars should enter a religious house of their choice, either as brothers or lodgers. His decree was occasioned by the situation in other countries, but was implemented in England, and some Templars transferred to other religious houses, although opposition was again expressed by monasteries. There were, however, some Templars in England who were never apprehended and lived out their lives in freedom.